Back of the envelope modelling of infectious disease transmission dynamics for veterinary students - Smith, Gary (Cambridge Scholars Publishing, 2019)
This book deals with how we construct and use deterministic mathematical models of the transmission of infectious diseases in domestic and wild animals. It is a manual, drawing on examples from the world of veterinary medicine, but will appeal to the interested reader from any background. Mathematical models of infectious disease transmission dynamics are increasingly used to inform population-based disease control strategies. Such strategies are typically implemented by clinicians (in both human and animal medicine), policy makers, and career civil servants. This book will be of value to all